Small Business Owners and Daily Recovery Experiences: The Link with Well-Being and Burnout - Mathieu Le Moal; Roy Thurik; Olivier Torrès; Guillaume Soenen (Institute of Labor Economics (IZA), 2024)
We analyse the links between daily recovery experiences after work (detachment, relaxation, mastery and control) and mental health (well-being and burnout) based on four surveys of French small business owners. First, comparing our results with those of employees' recovery experiences, we find that small business owners have fewer recovery experiences for all four dimensions. Second, controlling for gender, age, life partner, education level, executive experience, business size, capital ownership and type of entrepreneur, both linear regressions and SEM analysis show that the quality of overall daily recovery experiences increases well-being and reduces burnout. Third, we show that the detachment component is not correlated with well-being, and the mastery component is not correlated with burnout. Relaxation and control are most strongly associated with wellbeing, whereas control has the strongest association with burnout. Many implications (including clinical) are discussed.
Keywords: I12; I31; L26; 330; small business owners; entrepreneurs; daily recovery experiences; well-being; burnout; France